Wielkie zmiany w małym mieście. Dobre i złe spotkania z nowoczesnością w „Promieniu” Stefana Żeromskiego - Chyła, Karolina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
This article analyses complex and ambiguous aspects of modernisation, depicted by Stefan Żeromski in his intriguing but rather obscure novel “Promień” [“The Ray”] (1898). The writer chooses a provincial town for his scenery – although based on Kielce, it is hidden with a fictional name – which experiences an industrial revolution in miniature. A railroad built in the area, old, solid shops and enterprises brought to death by the modern way of trade and a shockingly radical local newspaper ran by the novel’s protagonists are just a few most striking symptoms of that inevitable and unsettling process of change.
Small Town, Great Changes – “Promień” [“The Ray”] by Stefan Żeromski and Multidimensional Modernity
Keywords: Stefan Żeromski; Promień [The Ray]; modernity; turn of the 19th and 20th century; nowoczesność; przełom XIX i XX w.